Somaclonal Variation in Oroxylum indicum (L.) Vent- an Endangered Tree Species - Yogendra K. Bansal, Mamta Gokhale* and (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Optimum callus formation was observed from apical buds or axillary buds of in vitro grown seedling on Murashige and Skoogsâ€™ (1962) medium supplemented with auxins 0.1-1 mg-1 of IBA, IAA, NAA and 2,4-D. Morphogenic callus was cultured on media supplemented with additives (CH & AgNO3 ) with BAP (1 mg-1). Maximum shoot regenerationÂ and elongation were achieved upon transferring the callus to medium containing BAP (1 mg-1) with AgNO3 (2 mg-1). Elongated shoots rooted on Â½ MSM supplemented with IBA (mg-1) with AgNO3 (1 mg-1). Shoots regenerated from this protocol exhibited somaclonal variation in different characters viz. leaf shape, node size.